Eletrocerâmicas multifuncionais ecologicamente corretas baseadas em (Bi0,5Na0,5)TiO3: a influência da dopagem doadora sobre suas propriedades físicas - Diaz, Julio Cesar Camilo Albornoz (2018)
In the current context of research that points to the development of ecologically correct materials highlights the fact that a single family of materials can not be obtained capable of mimicking all the properties of PZTs (systems based in Pb(Zr1-xTix)O3). However, some studies have generated new expectations regarding the possible multifunctionality in materials based on BNT ((Bi0.5Na0.5)TiO3), being that the doping in BNT and some compositions in the MPB of the BNT-xBT system (BT being the acronym for BaTiO3) with rare earths and some transition metals have shown improvements in some properties and the actual coupling between electrical and optical properties, thus leveraging the interest and diversification of the research on BNT based materials. The general objective was the study of BNT and BNT6 ([(Bi0.5Na0.5)0.94Ba0.06]TiO3, in the MPB of BNT-xBT system) doped with different elements, Sm3+ and La3+ acting as donor elements at position A and Nb5+ being a donor element at position B. The samples were produced by the solid state reaction method. A suitable processing route was determined for producing the studied samples of the systems BNT-100xSm, BNT6-100xSm, BNT6-100xLa and BNT6-100xNb, obtaining samples of high quality, high densification and absence of spurious or secondary phases. In all cases, it was carried out a study including structural characterization at room temperature and dielectric and mechanical characterisations (DMA and flexural) as a function of temperature and for several frequencies. Additional characterizations (TSD current, photoluminescence, and hysteresis P-E measurements) were used when required. It was possible to glimpse a general panorama for the BNT, presenting a consistent physical explanation of all the processes observed in the studied temperature range. In this case, mechanisms of mobility of ionic space charge were observed and described, that were not yet reported in the literature. For BNT6, frequency dependent processes were identified at high temperature through dielectric and mechanical measurements, suggesting the mobility of oxygen vacancies. Effects of substitution of Sm3+, La3+ and Nb5+ on BNT and BNT6 were analysed. X-ray diffraction patterns at room temperature reveal the stabilization of the tetragonal phase with addition of each dopant. Dielectric measurements and anelastic spectra show that the increase of the Sm or Nb content induces monotonous displacement to low temperature of the observed processes, in contrast La induces shifts with a non-monotonous tendency. The compositional disorder induced by addition of the dopant element generates, in all cases, changes in both the relative variation of the elastic modulus and the real part of the permittivity, which may indicate the deterioration of piezoelectric properties. As expected, Sm3+ doping generates photoluminescence. The anelastic and photoluminescence spectra allows us to state that the different mechanisms required for charge balancing in Sm3+ doping in BNT and BNT6 are the reduction of a small amount of Sm3+ together with the preferential substitution of Sm3+ in the Bi3+ position. It can be observed that the shift to low temperature of the processes observed in the dielectric and mechanical measurements, induced by the addition of Nb, occurs together with the consolidation of the tetragonal structure, which may allow the stabilization and correlation between polar nano-regions with phase P4bm in lower temperature, thus favouring the relaxor behaviour in the system BNT6-100xNb. The study of the P-E hysteresis loops as a function of temperature in the BNT6-100xNb system showed promising energy storage properties. Finally, a possible sequence in structural evolution with the addition of La can be indirectly indicated, the stabilization of a major tetragonal ferroelectric phase in BNT6-0.7La and BNT6-1La compositions was unexpectedly observed, which could explain the non-monotony observed in the measurements with the increase of La content.